Rheological research of the curing processes of the epoxy-amine compositions based on ED-20 resin - Pavlukovich N.; Leshtaev A.; Buryakov V.; Polikarpova I.; Orlov M.; Storozhuk I.; Nelyub V.; Borodulin A. (E3S Web of Conferences, 2023)
In this paper the rheological properties of various epoxy-amine compositions based on the ED-20 epoxy resin were studied. The effectiveness of curing accelerators from among tertiary and quaternary amines has been evaluated. The rheokinetics of the curing processes were studied by the method of rotational viscometry. The times to reach the gel point of the studied systems are determined.